Mucosal Immunity to Gut Fungi in Health and Inflammatory Bowel Disease - Sean L. Carlson; Liya Mathew; Michael Savage; Klaartje Kok; James O. Lindsay; Carol A. Munro; Neil E. McCarthy (Journal of Fungi, 2023)
The gut microbiome is a diverse microbial community composed of bacteria, viruses, and fungi that plays a major role in human health and disease. Dysregulation of these gut organisms in a genetically susceptible host is fundamental to the pathogenesis of inflammatory bowel disease (IBD). While bacterial dysbiosis has been a predominant focus of research for many years, there is growing recognition that fungal interactions with the host immune system are an important driver of gut inflammation. Candida albicans is likely the most studied fungus in the context of IBD, being a near universal gut commensal in humans and also a major barrier-invasive pathogen. There is emerging evidence that intra-strain variation in C. albicans virulence factors exerts a critical influence on IBD pathophysiology. In this review, we describe the immunological impacts of variations in C. lbicans colonisation, morphology, genetics, and proteomics in IBD, as well as the clinical and therapeutic implications.